2021
DOI: 10.3389/fneur.2021.724969
|View full text |Cite
|
Sign up to set email alerts
|

Increased Autoimmunity in Individuals With Down Syndrome and Moyamoya Disease

Abstract: Objective: To determine if elevated rates of autoimmune disease are present in children with both Down syndrome and moyamoya disease given the high rates of autoimmune disease reported in both conditions and unknown etiology of angiopathy in this population.Methods: A multi-center retrospective case-control study of children with Down syndrome and moyamoya syndrome, idiopathic moyamoya disease, and Down syndrome without cerebrovascular disease was performed. Outcome measures included presence of autoimmune dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This is supported the observed 4.34 times greater risk of relapse in individuals with neurodiagnostic study abnormalities (including early/accelerated mineralization and CSF abnormalities) which are indicative of potentially interferon driven immune dysregulation, a concept more well established in systemic disease presentations in persons with DS [15][16][17][18] . It has been established that individuals with DS are at great risk for a variety of autoimmune disorders [19][20][21][22][23][24][25] , and thus it would be reasonable to consider the brain as another potential target of immune dysregulation. This study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported the observed 4.34 times greater risk of relapse in individuals with neurodiagnostic study abnormalities (including early/accelerated mineralization and CSF abnormalities) which are indicative of potentially interferon driven immune dysregulation, a concept more well established in systemic disease presentations in persons with DS [15][16][17][18] . It has been established that individuals with DS are at great risk for a variety of autoimmune disorders [19][20][21][22][23][24][25] , and thus it would be reasonable to consider the brain as another potential target of immune dysregulation. This study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Down syndrome, neurofibromatosis type 1, and several other genetic mutations are associated with the genetic predisposition of MMS. 20 Sixteen genes and several pathways, including the Ras and MAPK, Notch, DNA repair, inflammasome, chromatin remodeling, actin remodeling, coagulation, and nitric oxide (NO) pathways, are involved in moyamoya angiopathy ( Figure 3 ). 7 Literature suggests that RNF213 is the primary gene associated with moyamoya angiopathy.…”
Section: Pathophysiology Of Moyamoya Disease and Its Neuropsychiatric...mentioning
confidence: 99%
“…Advancements in imaging techniques integrating DSA, MRI, and cerebrovascular reserve capacity have led to the recently validated Berlin grading system which has proven superior to the traditional Suzuki staging system. 20 , 21 This allows clinicians to evaluate the hemodynamic status while stratifying the individual risks associated with surgery, as opposed to basing clinical decisions strictly on cerebrovascular morphology. 20 , 21 Other researchers have suggested that quantitative MRI-based methods and Doppler may be beneficial in MMD diagnosis and evaluation.…”
Section: Neuroimaging Findings and Neuropsychiatric Outcomes In Moyam...mentioning
confidence: 99%
See 1 more Smart Citation
“…1C and D ). Other disorders associated with MMS, such as vasculitis ( 8 ), autoimmune disease ( 9 ), infection ( 10 ) and thrombophilia ( 11 ), were excluded through medical history, physical examination and relevant blood tests. The patient was duly diagnosed with moyamoya disease (MMD) with aneurysm rupture and bleeding.…”
Section: Case Reportmentioning
confidence: 99%